circCDYL2, Overexpressed in Highly Migratory Colorectal Cancer Cells, Promotes Migration by Binding to Ezrin - Li, Xiaomin; Wang, Jianjun; Long, Huaicheng; Lin, Weihao; Wang, Haowei; Chen, Yujia; Yuan, Qinzi; Li, Xuenong (Frontiers in Oncology, 2021)
Background: Colorectal cancer (CRC) is one of the most common malignancies with high mortality worldwide, particularly due to metastasis. However, there are no clinically available strategies for treating CRC metastasis. Exploring the mechanisms underlying CRC metastasis is the key to improve the treatment of CRC with metastasis. Methods: In this study, we generated the highly migratory CRC cell subline H-RKO using a repeated transwell migration assay to identify circRNAs involved in CRC migration by high throughput RNA sequencing. Upregulated circRNAs were validated by RT-qPCR to identify the most elevated circRNA. The expression of this circRNA (circCDYL2) was evaluated in forty pairs of CRC tissues and four CRC cell lines by RT-qPCR. Transwell migration and wound healing assays were performed to verify the function of circCDYL2 in cell migration. The cellular distribution of circCDYL2 was confirmed using PCR. RNA pulldown and RNA Immunoprecipitation were used to confirm the interaction between circCDYL2 and Ezrin. Western blotting, immunohistochemistry, and rescue experiments were used to determine the role of circCDYL2 in regulating Ezrin protein expression and AKT phosphorylation. Results: Among the candidate circRNAs, circCDYL2 was the highest overexpressed circRNA in H-RKO compared to parental N-RKO cells. Furthermore, circCDYL2 expression was elevated in CRC tissues and cell lines. Gain and loss of function assays indicated that circCDYL2 enhanced the migration of CRC cells. circCDYL2 was located in the cytoplasm of CRC cells and interacted with Ezrin to upregulate its protein levels, resulting in AKT phosphorylation. Ezrin knockdown abrogated the CRC cell migration induced by circCDYL2 overexpression. Conclusions: Our study demonstrated for the first time that circCDYL2 promotes CRC migration by binding Ezrin and activating the AKT pathway. CircCDYL2 represents a potential therapeutic target for preventing CRC metastasis.